Reevaluation of the Risk of Fetal Death and Malformation After Q Fever. (18th April 2014) - Million, Matthieu; Roblot, France; Carles, Dominiques; D'Amato, Felicetta; Protopopescu, Camelia; Carrieri, Maria Patrizia; Raoult, Didier
Abstract : A meta-analysis of 136 Q fever pregnancies, including 4 new cases and 7 population-based serological studies, revealed significant increases in fetal death and malformation after Q fever during pregnancy. This poor obstetric outcome is prevented by antibiotic treatment.